UPAYA GURU DALAM PEMBENTUKAN KEPRIBADIAN ISLAM PADA SISWA SEKOLAH DASAR ISLAM TERPADU IBNU ABBAS PEKANBARU - Rachmad, Ferizal; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this study was to determine the teacher's efforts in forming Islamic personality in SDIT Ibnu Abbas Pekanbaru students. This study used a descriptive method with data collection by observation and interviews. The results of this study are the teacher's efforts in forming Islamic personality in SDIT Ibnu Abbas Pekanbaru students covering several aspects including teaching about the personality of Rabbani, Malaki, Qurani, Rasuli, Yawm Akhiri, Taqdiri, Syahadatain, Mushalli, Sha'im, Muzakki, Hajji, behavior gratitude, patience, resignation, forgiveness, mutual respect, compassion and courtesy. The effort made is to provide an explanation to students in the learning process regarding the importance of the personality of a believer, Muslim and muhsin. The teacher also gives examples and encourages students to emulate good qualities in accordance with the explanation of the personality material of believers, Muslims and muhsins and applies them in everyday life both in the school environment and in the community environment.